PATHOLOGICAL ANATOMY OF BLOOD VESSELS OF PLACENTAL TISSUE OF PREGNANT WOMEN IN CORONAVIRUS INFECTION - Abdulloev Shakhboz Hamroevich; Babaev Khamza Hurmatovich; Omonov Shohruh Rakhimovich (Journals Park Publishing, 2024)
This article aims to explore the complex landscape of placental vascular pathology in the setting of maternal COVID-19 infection, and to highlight the challenges and opportunities for clinicians, researchers, and health professionals in protecting pregnant women and their well-being.
Keywords: coronavirus, pathological anatomy, blood vessels, placental tissue, placenta.